2013
DOI: 10.2304/eerj.2013.12.4.534
|View full text |Cite
|
Sign up to set email alerts
|

School Choice Policy: Seeking to Balance Educational Efficiency and Equity. A Comparative Analysis of 20 European Countries

Abstract: In recent years, the degree of choice in education systems has increased in most countries. Still, the variation of choice policies across countries is substantial. The authors ask under what combinations of conditions (i.e. institutional features of education systems) choice policy succeeds in balancing educational efficiency and equity. Using the fuzzy-set qualitative comparative analysis, they investigate the impact of seven institutional conditions in 20 European countries. Those seven conditions are ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…As much of the contemporary research on public education privatisation has been conducted around institutions where school competition and student’s free choice have been key ingredients (see e.g. Lauri and Põder, 2013; Lundahl et al, 2013; Verger et al, 2016), we see a need to conduct empirical research on the presence of private providers in public education that depart from this particular organisational set-up. Swedish MAE, which engages 4% of the adult population each year, is built around a system where state policy puts the responsibility and right of organising education in the hands of local actors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As much of the contemporary research on public education privatisation has been conducted around institutions where school competition and student’s free choice have been key ingredients (see e.g. Lauri and Põder, 2013; Lundahl et al, 2013; Verger et al, 2016), we see a need to conduct empirical research on the presence of private providers in public education that depart from this particular organisational set-up. Swedish MAE, which engages 4% of the adult population each year, is built around a system where state policy puts the responsibility and right of organising education in the hands of local actors.…”
Section: Resultsmentioning
confidence: 99%
“…As many researchers have shown, there are processes of endogenous privation parallel to exogenous privatisation, where language, logics and techniques from the private sector are introduced into the public sector (Ball and Youdell, 2008). One such introduction is the idea of competition, where schools should compete for students (Lauri and Põder, 2013; Lundahl et al, 2013). Such competition could be attained without virtually any private providers; for example, a system with only public schools but where students are free to choose any school they wish.…”
Section: Discussionmentioning
confidence: 99%
“…The discussion about the potential harm competition-oriented and marketbased solutions in education might cause has motivated scholars (Schütz, Ursprung, & Wößmann, 2008) to show that equality in educational opportunities is strongly influenced by the institutional set-up of countries education system. Following this literature, Lauri and Põder (2013) and many others have shown that educational efficiency and equity can be complementary (see Figure 7.1). However, this complementarity is very much dependent on the design of educational policy.…”
Section: 2mentioning
confidence: 78%
“…Paradoxically, the hoped ability of NPM to respond to the diverse needs fails, and the drive towards efficiency leads to a narrower approach to public service and stratified service delivery (Bevir, 2010;Lauri, 2013). While there are countries where NPM-led initiatives have been a clear political choice, in many countries, the principles of NPM emerge to the political agenda and/or pubic services more covertly (Lauri & Põder, 2013). In Estonia, the competitive entrance of some schools in Tallinn with entrance tests and prep-schooling is one of the examples of this hidden and covert route of NPM-led policies.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation